Analisis Yuridis Terhadap Proses Pendaftaran Kapal Untuk Mewujudkan Kepastian Hukum Status Kapal Pada Kantor Kesyahbandaran Dan Otoritas Pelabuhan Khusus Batam - Aliatul Hana, Nurul; Parameshwara, Parameshwara; Fadlan, Fadlan (Jurnal Syntax Fusion, 2022)
This study aims to find out and analyze the implementation of ship registration to realize legal certainty on ship status, factors that become obstacles or obstacles during the ship registration process at KSOP Batam. This research uses empirical or sociological normative research methods (applied law research) which is basically a combination with a normative approach (legal research), namely legal research regarding the application or implementation of normative legal provisions (codification, laws or contracts) in action on every certain legal event that occurs in society and in order to obtain primary data through field research (research). The results of the study show that legal arrangements for ship registration in Indonesia are contained in several laws and regulations, namely the Criminal Code, Law Number 17 of 2008 concerning Shipping, especially in Part Six which regulates the Legal Status of Ships from Article 158 to Article 161. Besides that, regulated in several implementing regulations, namely Government Regulation Number 51 of 2002 concerning Shipping and Minister of Transportation Regulation Number PM 13 of 2012 concerning Ship Registration and Nationality. In general it can be said that ship registration is so that every ship can always be identified throughout its operational life, therefore any changes to the name, ownership, size and specifications, other signs of the ship must be honestly reported to the ship registration official at the place where the ship is registered